2015
DOI: 10.3109/17435390.2015.1048322
|View full text |Cite
|
Sign up to set email alerts
|

Contact-dependent transfer of TiO2nanoparticles between mammalian cells

Abstract: Cellular organelles have been shown to shuttle between cells in co-culture. We hereby show that titanium dioxide (TiO2) nanoparticles (NPs) can be transferred in such a manner, between cells in direct contact, along with endosomes and lysosomes. A co-culture system was employed for this purpose and the NP transfer was observed in mammalian cells including normal rat kidney (NRK) and HeLa cells. We found that the small GTPase Arf6 facilitates the intercellular transfer of smaller NPs and agglomerates. Spherical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 80 publications
(99 reference statements)
2
11
0
Order By: Relevance
“…and ), and the smaller particle, that is, Ti5, was clearly associated with larger agglomerates and more adverse effects indicating that different NP sizes may elicit different toxicity responses. This was consistent with previous reports from our lab with regard to the uptake of Ti5 particles by different cell types . Internalization of both particles was associated with morphological changes in SaOS‐2 and the NP‐treated cells appeared smaller in size and in association with Ti5, the cells had a higher aspect ratio.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…and ), and the smaller particle, that is, Ti5, was clearly associated with larger agglomerates and more adverse effects indicating that different NP sizes may elicit different toxicity responses. This was consistent with previous reports from our lab with regard to the uptake of Ti5 particles by different cell types . Internalization of both particles was associated with morphological changes in SaOS‐2 and the NP‐treated cells appeared smaller in size and in association with Ti5, the cells had a higher aspect ratio.…”
Section: Discussionsupporting
confidence: 92%
“…This was consistent with previous reports from our lab with regard to the uptake of Ti5 particles by different cell types. 10,32 Internalization of both particles was associated with morphological changes in SaOS-2 and the NP-treated cells appeared smaller in size and in association with Ti5, the cells had a higher aspect ratio.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It was demonstrated that TiO 2 78, 79, 80 and Ag81 NMs induce an increase of SS signal in cell populations after exposure to both NMs. SS indicates the granularity of the cells and is strongly linked to their content of NMs.…”
Section: High‐throughput Flow Cytometrymentioning
confidence: 99%